Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
(4x + 7)² = 60
(4x + 7)(4x + 7) = 60
(4x² + 28x + 28x + 49) = 60
4x² + 56x + 49 = 60
-49 -49
4x² + 56x = 11
4x² + 56x - 11 = 11 - 11
4x² + 56x - 11 = 0
x = -56 +/- √(56² - 4(4)(-11))
2(4)
x = -56 +/- √(3136 + 88)
8
x = -56 +/- √(3174)
8
x = -56 +/- 56.34
8
x = -7 +/- 7.0425
x = -7 + 7.70425 x = -7 - 7.70425
x = 0.70425 x = -14.70425
(4x + 7)(4x + 7) = 60
(4x² + 28x + 28x + 49) = 60
4x² + 56x + 49 = 60
-49 -49
4x² + 56x = 11
4x² + 56x - 11 = 11 - 11
4x² + 56x - 11 = 0
x = -56 +/- √(56² - 4(4)(-11))
2(4)
x = -56 +/- √(3136 + 88)
8
x = -56 +/- √(3174)
8
x = -56 +/- 56.34
8
x = -7 +/- 7.0425
x = -7 + 7.70425 x = -7 - 7.70425
x = 0.70425 x = -14.70425
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.